Overtraining syndrome, stress and nutrition in football amateur athletes - Montesano, P.; Di Silvestro, M.; Cipriani, G.; Mazzeo, F. (Journal of Human Sport & Exercise, 2019)
In competitive sports is important optimizing and improving the recovery-stress state. We aimed to investigate the overtraining syndrome in the football, modulating the agonistic training and evaluating the nutritional status of the young amateur soccer players, thought monitoring of the capacity of endurance and strength in a sample of twenty athletes between the ages of 18 and 33 (mean 22 +/- 4.43 SD). Overtraining syndrome is a condition of physical, behavioural and emotional stress in sports and occurs when the physical activity is so intense as to prevent the athlete from performing a correct recovery totally eliminating the sense of fatigue. The athletes, from September 2016 to April 2017 were monitored with anthropometric tests (BMI calculation), nutritional tests (Recall test) and sportive (Cooper and Sargent test) to prevention of the overtraining syndrome with initial, intermediate and final measurements. Each player, during the observational period, performed normal athletic training sessions and participating two additional monthly sessions, for a total of sixteen sessions, with free overloads and, after intermediate verification, the exercises has been modified to reduce overtraining phenomenon. Tests initial results have been positive for defenders and midfielders while at the end of the search goalkeepers and forwards have significantly improved the performances. The total percentage increase of sample is around +/- 4% and the study confirmed that by modulating the intensity of training and controlling the athletes' diet, it is possible to reduce or eliminate overtraining effects.